Prosedur Production Control Pada Pt Astra Honda Motor Jakarta - Maya Sofiana (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2019)
This writing aims to know how to procedures of production control on PT Astra Honda Motor (PT AHM) on Jakarta. This writing is executed on PT AHM, with the methods of literature writing, observation, and interviews. The results of this writing is represent that, procedures of production control is still not suitable because it is still in development stage, so less than the maximum in the application of production planning, production control, and production actual. The procedures of production control on PT AHM Jakarta of production planning, production control, and production actual. The constraints faced is the procedures of production control on PT AHM Jakarta is difficult to implement prosedures for changing the order of planning on the day running, SFG lacks parts, there are parties who disagree about the minus burden. The solutions in facing is the procedures of production control on PT AHM Jakarta is in the case of production planning, in case of force, a change in order is permitted provided all parts are available, in the case of control production , in case of important.  In the case control production, SFG is allowed as long as it can be completed that day.  In the case actual production, disputing parties are accommodated, meetings with related parties.